Single Phase Power Factor Improvement Based Instantaneous Power P Q Theorm - Setiyono Setiyono; Bambang Dwinanto (Indonesian Scientific Journal, 2020)
This paper presents how to harmonic disturbance reduce on single phase power system. One of the most popular method is harmonic signal extraction with instantaneous power p q theorm. This algorithm implemented to harmonic cencellation by active power filter circuit be paralled with the non linier load. This filter generates of current compensation that are injected into the grid to improve power quality. This Filter is built by an inverter circuit that consists of a mosfet switch array and capasitor mounted on DC link side. Two types of loads are resitive inductive and resistive capasitive produce of current source wave form that close pure sinusoid. Simulation results show the THD index fell to the level of 2.7% in accordance with IEEE 519 standard rules which states that the harmonics content of the power system may occur below 4%, indicating that the power system can be categorized as having good quality.